Free vs. faithful - Hjort-Pedersen, Mette (ELOPE (Ljubljana), 2016)
For many years translation theorists have discussed the degree of translational freedom a legal translator has in rendering the meaning of a legal source text in a translation. Some believe that in order to achieve the communicative purpose, legal translators should focus on readability and bias their translation towards the target language community. Others insist that because of the special nature of legal texts and the sometimes binding force of legal translations, translators should stay as close to the source text as possible, i.e., bias their translation towards the source language community. But what is the relationship between these "academic" observations and the way professional users and producers, i.e., lawyers and translators, think of legal translation? This article examines how actors on the Danish legal translation market view translational manoeuvres that result in a more or less close relationship between a legal source text and its translation, and also the translator's power to decide what the nature of this relationship should be and how it should manifest itself in the translation.
Keywords: akademski kriteriji ocenjevanja; pravno prevajanje; prevajalske prototipične lastnosti; prevodoslovna teorija; teorija relevance; tržne preference pravnega prevajanja